(untitled) (Texas Journal of Medical Science, 2022)
the research analyzes the concentration of lactate and urea in rowers during the training process in different temperature conditions and a significant change in the concentration of these indicators when performing intense physical activity, training, especially in conditions of high temperature and solar insolation. Determination of the concentration of lactate and urea in the studied rowers during the training process in different temperature conditions indicates a significant change in the concentration of these indicators when performing intense physical activity. Carrying out training in sub-maximum and near-maximum aerobic loads in heat conditions leads to a deeper violation of blood circulation of working organs, in particular muscles. A decrease in blood supply under the influence of a double factor leads to the development of hypoxia, which leads to an increase in the anaerobic process in the energy production of muscles.